CORRELATION BETWEEN ANTIBIOTIC RESISTANCE PHENOTYPES WITH MOBILE GENETIC ELEMENTS (INTEGRON CLASS I) IN UROPATHOGENIC E. coli - Marwa Sh. M.,; A. H. Ibrahim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the relationship between Integron class I and multidrug resistance in Uropathogenic E. coli. A total of 302 urine samples were used in this study. 139 Uropathogenic E coli  were collected from hospitalized patients. Then, using biochemical testing and the Vitek II compact system, all of the isolates were diagnosed and confirmed. All E. coli isolates were tested using a disc diffusion procedure to detect their susceptibility to 23 types of antibiotics from different classes, and the result showed that these bacteria were  highly resistant to most used antibiotics especially, Cefotaxime, Ampicillin,  Piperacillin, Trimethoprim- sulfamethoxazole ,Cefepime and Ceftazidime, while the most effective antibiotics were Colistin and Tigecyclin. Also the results show different resistance patterns in which 111 (79.86%) isolate showed multidrug resistance MDR, Extensively drug resistance XDR 18  isolate (12.94%), while Pandrug resistance PDR 3 (2.15%). PCR was used to detect the presence of  integron class I in MDR isolates ,which was found in 87 of isolates with a 483 bp amplification product.  The resolved PCR products were sequenced in both directions (forward and reverse), and the NCBI BLASTn engine revealed 100% sequence similarity between the sequenced  samples and the planned reference1target sequences. These findings revealed that E. coli strains were highly resistant to common antibiotics; however, given the high prevalence of integron class I among these isolates, we can deduce that antibiotic resistance genes were most likely carried on mobile genetic elements (integron) in these isolates.